Never left behind chair - Khair, Nur Adilah; Mat Zaini, Nurul Syazwani; Yunus, Murfiqah Yasmin; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2018)
This chair was specially designed for left-handed person. However, both right-handed person and lefthanded person can use them. It gives justice to the left-handed group and comfort to the right-handed person. In other words, it was designed for everyone in this entire world. Last but not least, this product also can be used by handicap person because the product‟s features were also being made out of their considerations. The aim of this product is to let people gained knowledge despite their condition. Novelty and uniqueness: This product specially designed for left-handed person. It is easy for them to do assignment and writing tasks.